تأثير إستراتيجة التعليم التعاوني في تنمية قدرة الطلبة على الترجمة من العربية إلى الإندونيسية بمعهد منبع الصالحين كرسيك - Sabilar Rosyad, Muh; Qomaruddin, Farid; Sadli, Faishol (Lughatu Ad-dhat, 2024)
The phenomenon of Arabic-Indonesian translation in Islamic boarding schools is considered commonplace, this is often done in the middle of the learning process of Turath Book (classic books) which still adhere to the principle of word-for-word translation or literal translation. This study aims to determine the level of influence of cooperative learning strategies on students' ability to translate text from Arabic into Indonesian at the Mambaus Sholihin Islamic Boarding School. This study used a quantitative approach with a pre-experimental type of methodology. The number of samples is 40 students determined through the saturated sample technique. The data in this study were obtained through observation, testing and documentation techniques. Meanwhile, to test the hypothesis in this study, researchers used a paired sample test with the SPSS formula. The results of this study are that cooperative learning strategies influence improving students' ability to translate texts from Arabic into Indonesian. This is indicated by sample testing combined with a Sig.-2Sig score of 0.00 <0.05. Thus, it can be concluded that the alternative hypothesis is accepted, and null hypothesis is rejected. The level of influence of the cooperative learning strategy is 0.21 (very large) based on the Cohens formula.